UNLOCKING FINANCIAL INSIGHTS: EVALUATING PERFORMANCE THROUGH KEY RATIOS - Rani Rachmawati; Sri Sutrismi; Yunita Duwi Anggiyasari (Universitas Tulungagung, 2024)
This study analyzes the financial performance of Pabrik Gula Modjopanggoong through key financial ratios, including liquidity, activity, solvency, and profitability. Using financial data from 2019 to 2023, the study employs a descriptive quantitative approach to evaluate the company’s financial stability and operational efficiency. The findings reveal that liquidity ratios, such as Current Ratio and Quick Ratio, fall below industry standards, reflecting challenges in meeting short-term obligations. Activity ratios demonstrate poor asset utilization, with a low Total Asset Turnover (TATO), although inventory management, as measured by Inventory Turnover (ITO), is efficient. Solvency ratios, including Debt-to-Equity Ratio (DER) and Debt-to-Asset Ratio (DAR), show favorable values, indicating minimal reliance on debt. However, profitability ratios, such as Net Profit Margin (NPM) and Return on Assets (ROA), are suboptimal due to declining sales and high operational costs. These results highlight the need for improved asset management and operational strategies to enhance profitability and competitiveness. The study provides actionable insights for optimizing financial performance and ensuring long-term sustainability.